Induction and contribution of beta platelet‐derived growth factor signalling by hepatic stellate cells to liver regeneration after partial hepatectomy in mice. (21st September 2015) - Kocabayoglu, Peri; Zhang, David Y.; Kojima, Kensuke; Hoshida, Yujin; Friedman, Scott L.
Abstract: Background & Aims: Hepatic stellate cells (HSCs) activate during injury to orchestrate the liver's inflammatory and fibrogenic responses. A critical feature of HSC activation is the rapid induction of beta platelet‐derived growth factor (β‐PDGFR), which drives cellular fibrogenesis and proliferation; in contrast, normal liver has minimal β‐PDGFR expression. While the role of β‐PDGFR is well established in liver injury, its expression and contribution during liver regeneration are unknown. The aim of this study was to determine whether β‐PDGFR is induced during liver regeneration following partial hepatectomy (pHx), and to define its contribution to the regenerative response. Methods: Control mice or animals with HSC‐specific β‐PDGFR‐depletion underwent two‐thirds pHx followed by assessment of hepatocyte proliferation and expression of β‐PDGFR. RNA‐sequencing from whole liver tissue of both groups after pHx was used to uncover pathways regulated by β‐PDGFR signalling in HSCs. Results: Beta platelet‐derived growth factor expression on HSCs was up‐regulated within 24 h following pHx in control mice, whereas absence of β‐PDGFR blunted the expansion of HSCs. Mice lacking β‐PDGFR displayed prolonged increases of transaminase levels within 72 h following pHx. Hepatocyte proliferation was impaired within the first 24 h based on Ki‐67 and PCNA expression in β‐PDGFR‐deficient mice. This was associated with dysregulated growth in the β‐PDGFR‐deficient mice based on RNAseq with pathway analysis, and real‐time quantitative PCR, which demonstrated reduced expression of Hgf, Igfbp1, Mapk and Il‐6. Conclusions: Beta platelet‐derived growth factor is induced in HSCs following surgical pHx and its deletion in HSCs leads to prolonged liver injury. However, there is no significant difference in liver regeneration.